NEW ELECTROCHEMICAL METHOD FOR THE PREPARATION OF Pt/C NANOSTRUCTURED MATERIALS - Novomlinskij Ivan N. (Конденсированные среды и межфазные границы, 2017)
The original method for the preparation of dispersed Pt/C materials by means of platinum electrodeposition on the carbon particles in suspension has been proposed. The electrolysis was carried in galvanostatic conditions with vigorous stirring carbon suspension in platinum electrolyte. In the process of mixing microparticles of carbon occasionally have been in contact with the surface of the cathode. At the time of contact and getting into the cathode layer, providing a supply of electrons to the carbon particles due to the percolation effect, the microparticles of carbon “turned” into a part of the cathode, owing to what process of restitution of ions of platinum proceeded on their surface. The materials were studied by X-ray, thermogravimetry, cyclic voltammetry and scanning electron microscopy. The resulting Pt/C materials contain from 9 to 14 wt.% Pt. On the diffraction patterns of the synthesized samples clearly expressed characteristic reections for polycrystalline platinum, which con rms the presence of the metallic phase of platinum. The calculation showed that the average size of the crystallites of platinum, depending on the conditions of the electrolysis is from 7 to 15 nm. The value of electrochemically active surface area of the synthesized Pt/C materials, designed for the hydrogen region of the cyclic voltamperometry, ranging from 23 to 56 m2/g (Pt), depending on the conditions of obtaining materials and load platinum in them. The resulting materials exhibit catalytic activity in the oxygen electroreduction reaction which predominantly ows through 4-electron mechanism. Given the opportunities of the methods of electrocrystallization management processes of nucleation / growth of a new phase and, as a consequence, morphology of precipitate, our proposed method seems very promising for obtaining a dispersed Pt/C materials and electrocatalysts for low temperature fuel cells.